Increase in glutamate-induced neurotoxicity by activated astrocytes involves stimulation of protein kinase C - Ahlemeyer, Barbara; Kölker, Stefan; Zhu, Yuan; Hoffmann, Georg F.; Krieglstein, Josef (Journal of neurochemistry, 2002)
Activation of astrocytes is a common feature of neurological disorders, but the importance of this phenomenon for neuronal outcome is not fully understood. Treatment of mixed hippocampal cultures of neurones and astrocytes from day 2-4 in vitro (DIV 2-4) with 1 µm cytosine arabinofuranoside (AraC) caused an activation of astrocytes as detected by a stellate morphology and a 10-fold increase in glial fibrillary acidic protein (GFAP) level compared with vehicle-treated cultures. After DIV 12, we determined 43% and 97% damaged neurones 18 h after the exposure to glutamate (1 mm, 1 h) in cultures treated with vehicle and AraC, respectively. Dose-response curves were different with a higher sensitivity to glutamate in cultures treated with AraC (EC50 = 0.01 mm) than with vehicle (EC50 = 0.12 mm). The susceptibility of neurones to 1 mm glutamate did not correlate with the percentage of astrocytes and was insensitive to an inhibition of glutamate uptake. In cultures treated with vehicle and AraC, glutamate-induced neurotoxicity was mediated through stimulation of the NR1-NR2B subtype of NMDA receptors, because it was blocked by the NMDA receptor antagonist MK-801 and the NR1-NR2B selective receptor antagonist ifenprodil. Protein levels of the NR2A and NR2B subunits of NMDA receptor were similar in cultures treated with vehicle or AraC. AraC-induced changes in glutamate-induced neurotoxicity were mimicked by activation of protein kinase C (PKC), whereas neuronal susceptibility to glutamate was reduced in cultures depleted of PKC and treated with AraC suggesting that the increase in glutamate toxicity by activated astrocytes involves activation of PKC.
Gesehen am 28.12.2020